Digital Literacy Index of Teenagers in Indonesia - Nugroho, Catur; Nasionalita, Kharisma (Jurnal Pekommas, 2020)
Digital literacy as an ability to understand and use information from various digital sources is not only related to reading characters, but also the process of thinking and evaluating information found in digital sources. There are various issues related to this, such as hoaxes, privacy violations, cyberbullying, violent content, and pornography. This study aims to determine the digital literacy index of adolescents in Indonesia. In this study, the population taken is part of the new millennial generation, namely young people of high school age in four cities in Indonesia, namely Bandung, Surabaya, Pontianak, and Denpasar, with a sample size of 500 people each. With a quantitative approach and survey research methods, the results show that the digital literacy level of adolescents in the four cities is at an advanced level. The dimension of the ability to find and select information is the dimension with the highest value in each of these cities. The dimension of creativity, namely the ability of youth to produce and share creative content in digital media, is the dimension with the lowest value, but is still at an advanced level. With these results, it can be seen that teenagers in four cities can use technology and digital media quite well to communicate, be creative, and find and choose the right information.